BLOODSTREAM INFECTION WITH OLIGELLA UREOLYTICA IN INFANT: A CASE REPORT AND REVIEW OF LITERATURE - B, APOORVA; KHAN, ZARINE; SARWAT, TARANA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Oligella ureolytica is rarely involved as human pathogen but it is emerging as pathogenic bacteria. It is not commonly recovered from clinical specimens but when recovered, it is mostly from urinary and respiratory tract specimens as commensal organisms, but hardly from blood samples. We present here a case of O. ureolytica related bacteremia in a 1-month-old infant as a pure culture and we review the literature of previously reported cases of Oligella infections.